2022
DOI: 10.1001/jamanetworkopen.2022.6250
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Service Use, Suicide Behavior, and Emergency Department Visits Among Rural US Veterans Who Received Video-Enabled Tablets During the COVID-19 Pandemic

Abstract: IMPORTANCE Suicide rates are rising disproportionately in rural counties, a concerning pattern as the COVID-19 pandemic has intensified suicide risk factors in these regions and exacerbated barriers to mental health care access. Although telehealth has the potential to improve access to mental health care, telehealth's effectiveness for suicide-related outcomes remains relatively unknown. OBJECTIVETo evaluate the association between the escalated distribution of the US Department of Veterans Affairs' (VA's) vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 42 publications
(91 reference statements)
1
24
0
Order By: Relevance
“…Universal screening likely lowered these barriers for Veterans in rural areas and led to increased likelihood of being screened/evaluated across both mental and non-mental health settings, as suggested by our exploratory sub-analyses ( S3 Table ). VA’s use of virtual care may have further contributed to leveling the field across rural and urban Veterans by increasing access to virtual care for rural Veterans [ 33 ]. Future studies should explore potential mechanisms by examining rural-urban differences in care settings (whether mental health or other) where screens/evaluations occurred and by determining whether rural Veterans were more likely to get screened/evaluated via telehealth modalities.…”
Section: Discussionmentioning
confidence: 99%
“…Universal screening likely lowered these barriers for Veterans in rural areas and led to increased likelihood of being screened/evaluated across both mental and non-mental health settings, as suggested by our exploratory sub-analyses ( S3 Table ). VA’s use of virtual care may have further contributed to leveling the field across rural and urban Veterans by increasing access to virtual care for rural Veterans [ 33 ]. Future studies should explore potential mechanisms by examining rural-urban differences in care settings (whether mental health or other) where screens/evaluations occurred and by determining whether rural Veterans were more likely to get screened/evaluated via telehealth modalities.…”
Section: Discussionmentioning
confidence: 99%
“…We examined changes in video visits and changes in visits across all modalities of care (video, phone, and in-person) for these services among SUD-diagnosed tablet-recipients vs. SUD-diagnosed non-recipients before and after tablet-receipt. SUD psychotherapy visits were defined using Current Procedural Terminology (CPT) codes and SUD diagnosis codes, following prior work ( Gujral et al, 2022 ). SUD group therapy visits were visits for group evaluation, consultation, follow-up, and treatment provided by a VA facility's formal SUD Treatment Program ( U.S. Department of Veterans Affairs, n.d. ) and SUD individual outpatient visits were individual visits for evaluation, consultation, follow-up and treatment provided by the SUD Treatment Program.…”
Section: Discussionmentioning
confidence: 99%
“…Together, these patterns suggest that in many cases, video visits replaced in-person visits. Prior work has noted the clinical importance of such increases in psychotherapy ( Gujral et al, 2022 ) and group therapy for SUD care ( Oesterle et al, 2020 ) and the importance of continuation of SUD care when in-person services were declining ( Oesterle et al, 2020 ). These results indicate that VA's distribution of tablets facilitated continuity of SUD care among tablet-recipients through video telehealth during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that telephone appointments might negatively impact one's ability to disclose their substance use, since assessment often relies on nonverbal cues that are easier to get during in‐person visits or video appointments, where the veteran is visually observed 22 . A recent study found video‐enabled tablets were associated with a 20% reduction in emergency room visits during COVID‐19 among rural veterans with a history of mental health care; 27 distribution of tablets to veterans also resulted in increased utilization of psychotherapy visits and reductions in suicidal behaviors. Pandemic‐related stress can impact individuals coping with SUD, as stress, isolation, poor coping, and poor access to recovery‐based group meetings, can all culminate in cravings, preoccupation with use, and return to use, particularly among those in early recovery 28 …”
Section: Discussionmentioning
confidence: 99%